Pengaruh Penggunaan Buku Referensi Bioetika Terhadap Pemahaman Materi Bioteknologi Terintegrasi Agama Islam Peserta Didik Kelas XII MIA Madrasah Aliyah Darul Aminin NW Aik Mual - Muh. Zaini Hasanul Muttaqin (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the effect of the use of bioethics reference books on the understanding of Islamic religious integrated biotechnology topic in XII grade science student (MIA) of MA Darul Aminin NW Aik Mual. This study uses a Quasi Experimental Design research method. The population in this study were students of XII grade science student, totaling 52 students. The research sample was students of A class of XII grade science student (XII MIA.A), as the experimental group, totaling 26 students and students of class XII MIA.B as the control group, totaling 26 students. The sampling technique used is simple random sampling. The research instrument used was a test, consisting of a pre test and a post test. The results showed that the pre-test and post-test scores of the experimental class were better than the control class. The N-gain value of the experimental class is better than the control class. The results showed that there was an effect of the use of bioethics reference books on the understanding of integrated biotechnology topic in Islam in XII grade science student of MA Darul Aminin NW Aik Mual.